ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA PT KARANG BALI ASLI TUR - Dwipayana, I Made Garbadinata; Dewi, A. A. Sagung Kartika (E-Jurnal Manajemen, 2016)
The study aims to analyze the factors affecting the performance of employees at PT. Asli Bali reef tours and influencing variables that represent each of the factors affecting the performance of employees at PT. Karang Bali Asli Tur. Selecting and focusing the study on PT. Asli Bali reef tour with employees making as many as 66 people as the sample with saturated sample method. Data were collected through questionnaires and adopt a multiple linear regression analysis. Results of data through methods Principal Component Analysis (PCA), there are four factors that affect the performance of employees at PT. Asli Bali reef tour and was able to explain all the variants that exist in the data, that is equal to 66.150 percent. These four factors are leadership factor with eigen value of 3.826, the motivational factors with eigen value of 3.506, the compensation factor with eigen value of 3.012, and the communication factor with eigen value equal to 2.886. While the variables that represent each of the factors affecting the performance of employees at PT. Asli Bali reef tour is the discipline variable loading factor superior to 0.810, variable working relationship with the loading factor 0,795, variable holiday allowances with loading factor 0.815, and variable discussion with loading factor 0.886
Keywords: kepemimpinan; motivasi; kompensasi; komunikasi; kinerja